2023
DOI: 10.1021/acsaem.3c01997
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Templated Synthesis of Three-Dimensional B-Doped NiCoP Hollow Nanorod Arrays for Highly Efficient and Stable Natural Seawater Splitting

Chi Nghia Nguyen,
Thuy Tien Nguyen Tran,
Thuy-Kieu Truong
et al.

Abstract: Seawater electrolysis represents a sustainable route for the mass production of high-purity hydrogen fuel. However, the sluggish kinetics of the cathodic hydrogen evolution reaction (HER) remains an excellent challenge for large-scale applications, especially in industrial-level current densities. Here, we report a general strategy to activate three-dimensional (3D) NiCoP hollow nanorod arrays through boron doping, creating high-valence metal centers that are favorable for the water dissociation step. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, much effort has been made to explore global, cost-effective, and durable electrocatalysts for high-performance seawater electrolysis and, thus, renewable and sustainable hydrogen energy. The growing number of scientific studies on transition-metal-based compound catalysts have drawn a great deal of attention with abundant and outstanding performance electrocatalysts, such as oxides, sulfides, phosphides, selenides, carbides, nitrides, and so forth. Nevertheless, all these nonprecious catalysts are recognized as hardly achieving thriving activity and stability in scaling up applications, which remains a significant challenge. Therefore, investigating highly active and stable catalysts for seawater electrolysis is desirable and essential for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort has been made to explore global, cost-effective, and durable electrocatalysts for high-performance seawater electrolysis and, thus, renewable and sustainable hydrogen energy. The growing number of scientific studies on transition-metal-based compound catalysts have drawn a great deal of attention with abundant and outstanding performance electrocatalysts, such as oxides, sulfides, phosphides, selenides, carbides, nitrides, and so forth. Nevertheless, all these nonprecious catalysts are recognized as hardly achieving thriving activity and stability in scaling up applications, which remains a significant challenge. Therefore, investigating highly active and stable catalysts for seawater electrolysis is desirable and essential for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of alien elements was found to be an advancing strategy to improve catalytic performance via electronic structure modulation and heterojunction formation. Anions, such as P, N, S, and F, are usually doped into the matrix by replacing or substituting host materials to reconstruct the catalyst to improve electrical conductivity and provide a more active phase of catalysts. For example, the anion doped of sulfur and selenide in a solid solution of CoFe layered double hydroxide shows a significantly enhanced electrocatalytic performance toward the OER compared with its host . They found that anion doping induced fast electron transfer and low diffusion resistance and exposed more active sites, which contributed to the high catalytic activity.…”
Section: Introductionmentioning
confidence: 99%